Substituted 3-styryl-2-pyrazoline derivatives as an antimalaria : synthesis, in vitro assay, molecular docking, druglikeness analysis, and ADMET prediction - Linda Ekawati,; Beta Achromi Nurohmah,; Syahri, Jufrizal; Purwono, Bambang (Penerbit Universiti Kebangsaan Malaysia, 2022)
The synthesis, in vitro antimalarial assay, molecular docking, drug-likeness analysis, and ADMET prediction of substituted 3-styryl-2-pyrazoline derivatives as antimalaria have been conducted. The synthesis of N-phenyl (1a‒3a) and N-acetyl-substituted (1b‒3b) 3-styryl-2-pyrazolines was carried out using dibenzalacetone derivatives and hydrazine hydrate or phenylhydrazine. An in vitro antimalarial assay was conducted against the chloroquine-sensitive Plasmodium falciparum 3D7 strain, while molecular docking was performed toward the crystal protein of Plasmodium falciparum dihydrofolate reductase-thymidylate synthase (PfDHFR-TS) (PDB ID: 1J3I). Furthermore, the prediction of drug-like properties was determined by assessing Lipinski’s rules, and the pharmacokinetic parameters were also studied in-silico, including absorption, distribution, metabolism, excretion, and toxicity (ADMET). The in vitro assay showed that 3a (IC50 0.101 µM) has excellent antimalarial activity, followed by 2a (0.177 µM), and 1b (0.258 µM). Molecular docking has supported the in vitro assay by showing the lowest CDOCKER energy for 3a (‒56.316 kcal/ mol), then 2a (‒51.2603 kcal/mol), and 1b (‒48.8774 kcal/mol). The drug-like properties showed that all of the prepared compounds were acceptable based on Lipinski’s rules and predicted to be potentially orally bioavailable. The ADMET analysis provided information that 3a and 2a could be proposed as the best lead antimalarial drugs with further modification to reduce the lipophilicity and toxicity properties.